Synthesis, characterization, surface analysis, optical activity and solvent effects on the electronic absorptions of Schiff base-functionalized amino thiophene derivatives: Experimental and TD-DFT investigations - Kifah S.M. Salih (17269120) (2021)
New derivatives of 3,3′-di-(((E)-(5-substituted-thiophen-2-yl)methylene)amino)-N-methylpropylamines (3a,b) were synthesized from the dehydration of N-methyl-diaminopropylamine and 2-thielylcarboxaldehyde derivatives; spectroscopically characterized by 1H- and 13C-NMR, IR, LC-MS, UV-Vis and elemental analysis. The nature of the electronic transitions of the SB compounds was investigated using Time-Dependent Density-Functional Theory (TD-DFT). Surface analysis and influence of solvent polarity on spectral properties were examined and established consequently. The molecular electrostatic potential (MEP) revealed that the two geometrical structures were found to be quite similar in term of electronic distributions. The presence of different electrophilic and nucleophilic sites located on the surfaces was suggested to stabilize the structures via classical H-bond and non-classical C-H…π interactions, in addition to interact with assorted solvent molecules. On the other hand, the solvatochromism of compound 3b revealed a gradual shift to the red region through the increase of the solvent polarity, recording a 12 nm of bathochromic shift. The solvation relationship between the experimental λmax and Gutmann's donicity numbers displayed a sense of positive linear behavior with a fluctuation, which was ascribed to a week interaction between molecules of solute and selected solvent. The band gap energy of compound 3a was evaluated experimentally and computationally. Using optical absorption spectra, a value of ‒ 3.801 eV was estimated following Tauc approach, while ‒ 3.720 eV was resulting from TD-DFT simulation. Other Information Published in: Journal of Molecular Structure License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.molstruc.2021.131267